Cannabidiol Activates Neuronal Precursor Genes in Human Gingival Mesenchymal Stromal Cells. Issue 6 (29th December 2016) - Soundara Rajan, Thangavelu; Giacoppo, Sabrina; Scionti, Domenico; Diomede, Francesca; Grassi, Gianpaolo; Pollastro, Federica; Piattelli, Adriano; Bramanti, Placido; Mazzon, Emanuela; Trubiani, Oriana
ABSTRACT: In the last years, mesenchymal stromal cells (MSCs) from oral tissues have received considerable interest in regenerative medicine since they can be obtained with minimal invasive procedure and exhibit immunomodulatory properties. This study was aimed to investigate whether in vitro pre‐treatment of MSCs obtained from human gingiva (hGMSCs) with Cannabidiol (CBD), a cannabinoid component produced by the plant Cannabis sativa, may promote human gingiva derived MSCs to differentiate toward neuronal precursor cells. Specifically, we have treated the hGMSCs with CBD (5 µM) for 24 h in order to evaluate the expression of genes involved in cannabidiol signaling, cell proliferation, self‐renewal and multipotency, and neural progenitor cells differentiation. Next generation sequencing (NGS) demonstrated that CBD activates genes associated with G protein coupled receptor signaling in hGMSCs. Genes involved in DNA replication, cell cycle, proliferation, and apoptosis were regulated. Moreover, genes associated with the biological process of neuronal progenitor cells (NCPs) proliferation, neuron differentiation, neurogenesis, and nervous system development were significantly modulated. From our results, we hypothesize that human gingiva‐derived MSCs conditioned with CBD could represent a valid method for improving the hGMSCs phenotype and thus might be a potential therapeutic tool in the treatment of neurodegenerative diseases. J. Cell. Biochem. 118: 1531–1546, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We hypothesize that human gingiva‐derived mesenchymal stem cells conditioned with Cannabidiol could represent a valid method for improving their phenotype and thus might be a potential therapeutic tool in the treatment of neurodegenerative diseases. Genes involved in DNA replication, cell cycle, proliferation, and apoptosis were regulated by cannabidiol administartion in human gingiva‐derived mesenchymal stem cells.